Zginanie Luków Segmentowych - Borkowski, S. (Engineering Transactions, 1965)
The author presents an approximate method for solving the bending problem of segment archse.The problem is solved by assuming that the number of segments is two or more. Structural orthotropy is assumed. It is also assumed that the section forces Q,N1 and M2 are zero and that 1+λcosϕ≈1. The arch is subjected to a bending moment. The point od departure is the equations of a circularly symmetric state of the theory of orthotropic shells, that is Eqs. (4.1). Of the orthotropy functions the only important is the function k12 [Eq. (3.2)] which, after simplifying may be represented by (3.11). The parameters q0, q2, … of the latter equation are obtained from the diagram of Fig. 3 for a value of p, (3.10)3, previously determined. The fundamental equations from which the coefficients of the stress series (4,7) are obtained, are (4.9) and (4.12). The Kármán number is obtained from (4.13).Sec, 6 contains two numerical examples (Table 3, 4, Figs. 4 and 6). The arches have been tested experimentally by A. A. SKVORTSOV [2]. His results are presented in Figs. 5 and 7.